2014
DOI: 10.1038/srep05997
|View full text |Cite
|
Sign up to set email alerts
|

Ship-in-a-bottle synthesis of amine-functionalized ionic liquids in NaY zeolite for CO2 capture

Abstract: CO2 capture on solid materials possesses significant advantages on the operation cost, process for large-scale CO2 capture and storage (CCS) that stimulates great interest in exploring high-performance solid CO2 adsorbents. A ship-in-a-bottle strategy was successfully developed to prepare the [APMIM]Br@NaY host–guest system in which an amine-functionalized ionic liquid (IL), 1-aminopropyl-3-methylimidazolium bromide ([APMIM]Br), was in-situ encapsulated in the NaY supercages. The genuine host-guest systems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…30 To overcome these drawbacks, a new strategy named supported ILs (SILs) has been proposed, 31,32 where ILs were encapsulated into porous solids to improve separation efficiency. 33 During the past decades, metal-organic frameworks (MOFs) have attracted tremendous attention due to their many unique properties such as high surface area, large pore volume and designable structure. [34][35][36][37][38] Some experimental and theoretical studies have shown that MOFs could be used as potential porous supporter for ILs.…”
Section: Introductionmentioning
confidence: 99%
“…30 To overcome these drawbacks, a new strategy named supported ILs (SILs) has been proposed, 31,32 where ILs were encapsulated into porous solids to improve separation efficiency. 33 During the past decades, metal-organic frameworks (MOFs) have attracted tremendous attention due to their many unique properties such as high surface area, large pore volume and designable structure. [34][35][36][37][38] Some experimental and theoretical studies have shown that MOFs could be used as potential porous supporter for ILs.…”
Section: Introductionmentioning
confidence: 99%
“…IL confined in pores of a zeolite is generally stabilized presenting a higher decomposition temperature in TGA. 4 When comparing thermograms of adsorption in H-MOR and NH 4 -MOR, Fig. 2(b) dashed line shows that H-MOR only contains water in its pores since only one weight loss between 25 and 250 ∘ C is observed in the thermogram.…”
Section: Resultsmentioning
confidence: 97%
“…This latter weight loss can be related to IL decomposition. IL confined in pores of a zeolite is generally stabilized presenting a higher decomposition temperature in TGA …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations